A MODEL OF ECOLOGICAL EDUCATION IN A HIGHER EDUCATION INSTITUTION - Savriyeva Iqbol Bahodirovna (American Journals Publishing, 2023)
In this article, a model of providing professional-personal environmental education to students in a higher education institution has been developed. Also, in the process of acquiring theoretical and practical knowledge, concepts such as a holistic attitude towards nature, a responsible attitude towards one's professional activities, and the feeling of being a part of nature are illuminated. In particular, the continuous professional-personal education model was used in practice.
Keywords: Ecological education, ecological competence, ecological knowledge, ecological culture, traditional pedagogical model.